Gut microbiota response to sulfated sea cucumber polysaccharides in a differential manner using an in vitro fermentation model. (October 2021) - Liu, Zhengqi; Zhang, Yujiao; Ai, Chunqing; Wen, Chengrong; Dong, Xiuping; Sun, Xiaona; Cao, Cui; Zhang, Xueqian; Zhu, Beiwei; Song, Shuang
Graphical abstract: Highlights: Microbial consortiums from different individuals response discrepantly to SCSP sj . Parabacteroides distasonis plays a critical role in SCSP sj utilization. More beneficial metabolites were accumulated by microbiota consuming more SCSP sj . Abstract: Sea cucumber Stichopus japonicus has been consumed as high-valued seafood in Asian, and its sulfated polysaccharide (SCSP sj ) has been inferred to benefit the host health via modulating gut microbiota composition. The present study compared the responses of gut microbiota communities from different donors to SCSP sj, and the key bacteria were identified by 16S rRNA gene sequencing analysis and in vitro fermentation with specific bacteria. Gut microbiota communities from 6 donors (A ~ F) utilized the polysaccharides to different degrees in vitro fermentation. Further comparison of Samples A and C demonstrated that Sample C with the relatively strong SCSP sj utilization capability possessed more Parabacteroides while Sample A contained more Bacteroides . Further in vitro fermentation of SCSP sj with 10 Parabacteroides and Bacteroides species suggests that Parabacteroides distasonis, enriched in Sample C, plays a critical role in the utilization of the polysaccharides. Moreover, short chain fatty acids and the metabolite profiles of Samples A and C were also compared, and the results showed that more beneficial metabolites were accumulated by the microbiota community consuming more sulfated sea cucumber polysaccharides. Our findings revealed that certain key members of gut microbiota, such as Parabacteroides distasonis, are critical for SCSP sj utilization in gut so as to influence the benefits of the polysaccharide supplement for host. Thus, to obtain better functional outcome for sulfated sea cucumber polysaccharides and sea cucumber, more attention needs to be paid to the effects of inter-individual differences in microbiota community structure.